Penerapan Personal Selling dalam Proses Komunikasi Pemasaran Lavanda Brownies Karawang - Nada Heriana; Yanti Tayo; Rastri Kusumaningrum (Masyarakat Ekonomi Syariah Bogor, 2025)
The implementation of personal selling strategies is a vital element in establishing effective marketing communication for SMEs, including Lavanda Brownies Karawang. This study aims to deeply analyze the application of personal selling strategies, both offline and online, and their contribution to product marketing success. Using a qualitative descriptive approach, data were collected through in-depth interviews, observations, and documentation. The findings reveal that offline personal selling strategies include product sampling, participation in bazaars, open table programs, and partnerships with resellers. These strategies foster personal relationships with consumers, enhance trust, and expand market reach. Meanwhile, online strategies leveraging platforms such as Instagram, Facebook, and TikTok effectively reach a broader audience. The combination of offline and online approaches is the key to Lavanda Brownies' success in creating consumer loyalty and strengthening brand image. These findings highlight that personal selling is not merely a sales method but a business philosophy focused on customer experience. This research offers practical contributions to SMEs in developing innovative marketing communication strategies to address competitive market challenges.